Prevention group for relapse from alcohol and other drugs - Kantorski, Luciane Prado; Lisboa, Liliane de Mello; Souza, Jacqueline de (SMAD Revista Eletrônica Saúde Mental Álcool e Drogas (Edição em Português), 2005)
This article reports on the experience of holding weekly group meetings for the prevention of relapses from alcohol and other psychoactive drugs at a Psychosocial Care Center, which started in November 2002. A cognitive-behavioral approach was adopted as a theoretical reference framework for conducting the meetings, starting from the motivation for treatment, after which an inventory was applied to identify abilities to handle situations with a potential risk of relapse.